CFD modeling of fluid-structure interaction for oscillating flexible risers (2007)
ABSTRACT: The dynamic response of an oscillating flexible riser involves a coupled phenomenon in which the nature and magnitude of the fluid forces acting on the riser highly depend on the structural riser's response. Therefore, the development of a response prediction model for oscillating flexible risers must consider the numerical modeling of fluid-structure interaction. In this paper a response prediction model for oscillating flexible risers using CFD-derived force coefficients is presented. A 20-meter riser model, sinusoidally excited at its top end using six different values of tension forces, is employed for its experimental validation. The computed maximum amplitudes in both in-line and cross-flow directions show good agreement with the experimental data considering the range of error commonly accepted for such implementations.